(untitled) (Revista de História da UEG (REVHIST), 2023)
Quirinópolis, municipality located in the countryside of the state of Goiás, experienced, in the last 30 years, a noticeable urban growth, process that changed meaningfully the landscape and the environment of the city. Taking this fact into account, this paper aims to reflect comparatively about the local historical heritage and about the places that are now quite frequented, from the approach of the cities History, and with a perspective linked to the transformations of the urban environment. The population growth, the emergence of new neighborhoods, and the transformation of spaces for leisure and coexistence, significantly modify the relationship with the historical references of the city. The coexistence of native populations and the migrant populations constitutes two kinds of memory: that from the ones who experienced the history of the city, and that from those who arrived in recent decades and have a different perception about places and their meanings. To reflect about the changes of perception in the urban environment with the focus on the historical heritages and the potential new places to acquire this meaning, we use an analysis of Quirinópolis urban area, through the system SIG QGIS 3.2.2 (geoprocessing). Keywords: Urban environment. Heritage. Memory. Quirinópolis-GO. Geoprocessing.